Poverty in Rural and Semi-Urban Mexico during 1992-2002 - Verner, Dorte (World Bank, Washington, DC, 2012)
This paper analyzes poverty in rural and semi-urban areas of Mexico (localities with less than 2,500 and 15,000 inhabitants, respectively) and provides guidance on a social agenda and poverty alleviation strategy for rural Mexico. The analyses are based on INIGH and ENE data sets for 1992-2002. Monetary extreme poverty affected 42 percent of the rural dwellers in dispersed rural areas and 21 percent in semi-urban areas in 2002, slightly less than one decade earlier. Most of the rural poor live in dispersed rural areas and 13.2 million people live in poverty in rural Mexico with less than 15,000 inhabitants. It is disproportionately a feature of households whose main job is in the agricultural sector, as self-employed farmers or rural laborers, and that have at most a primary education. However, the incidence of extreme rural poverty has declined since 1996 but at a slower pace than the decline in urban poverty. Hence, the rural-urban poverty gap increased in recent years and in some places extreme poverty is at least four times higher in rural than in urban areas. Moreover, not only is the income gap in urban areas increasing, but also the gap between richer and poorer segments of the population in the rural areas is growing. Finally, the gap between rich and poor regions is still large.